Micromorphology of cryoconite on Garabashi and Skhelda glaciers and soils of Baksan Gorge, Mt. Elbrus, Central Caucasus - Abakumov, Evgeny; Tembotov, Rustam; Kushnov, Ivan; Polyakov, Vyacheslav (Polish Polar Research, 2021)
In the Central Caucasus region, the intense process of deglaciation is identified as caused by cryoconite formation and accumulation. The fine earth materials were collected on the surfaces of Skhelda and Garabashi glaciers as well as from zonal soils of Baksan Gorge and were studied in terms of chemical, particle-size, and micromorphological features. Supraglacial sediments are located at the glacial drift area of material and, thus, due to transfer of these sediments to the foothill area, their fine earth material can affect micromorphological and chemical characteristics of adjacent zonal soils. Thin sections of mineral and organo-mineral micromonoliths were analyzed by classic micromorphological methods. Data obtained showed that the weathering rates of cryoconite and soil minerals are different. The cryoconite material on the debris-covered Skhelda Glacier originated from local massive crystalline rocks and moraines, while for Garabashi Glacier the volcanic origin of cryoconite is more typical. Soils of Baksan Gorge are characterized by more developed microfabric and porous media, but their mineralogical composition is essentially inherited from sediments of glacial and periglacial soils. These new data could be useful for understanding the process of evolution of the mineral matrix of cryoconite to the soil matrix formed at the foot of the mountain.